2015
DOI: 10.1002/etep.2167
|View full text |Cite
|
Sign up to set email alerts
|

Smart energy-consumption management system considering consumers' spending goals (SEMS-CCSG)

Abstract: Summary The goal of this paper is to optimize energy consumption, with minimum consumer interaction, and least impact on his/her life style, comfort and convenience. In the literature different demand side management (DSM) schemes are employed for consumer demand management. Till now, to the best of our knowledge none of researchers considered the consumers preferences, priorities, ease of use, grid stability, deviation minimization, demand curve flattening and implantation cost, collectively in a single manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…The constraints shown in (10) will assure minimum peak to average power ratio (PAPR). The PAPR is given by P AP R = peak demand of microgrid average demand of microgrid ∀ v, t (11) In equation 11, if the value of the nominator is reduced then PAPR will also be reduced. Moreover, while limiting the peak demand, the line losses will be also reduced.…”
Section: If the Starting Time Slot For Washing Machine Operation Ismentioning
confidence: 99%
See 1 more Smart Citation
“…The constraints shown in (10) will assure minimum peak to average power ratio (PAPR). The PAPR is given by P AP R = peak demand of microgrid average demand of microgrid ∀ v, t (11) In equation 11, if the value of the nominator is reduced then PAPR will also be reduced. Moreover, while limiting the peak demand, the line losses will be also reduced.…”
Section: If the Starting Time Slot For Washing Machine Operation Ismentioning
confidence: 99%
“…This redistribution of demand curve minimizes the peak demand of each microgrid which helps to curtail the PAPR. This peak clipping not only reduces the distribution losses but also plays an important role in PAPR reduction shown in equation (11).…”
Section: A Case Studiesmentioning
confidence: 99%
“…36 The main problem is that the WPP intermittent happens during the peak load hours and therefore, the DSM technologies can be considered to reduce the consumption in such hours. 37 For this reason, this article proposes a collaborative FACTS and DR program to alleviate the congestion of wind integrated transmission networks under the liberalized electricity market. In doing so, a practical case study based on the modified IEEE 24-bus reliability test system (RTS), as shown in Figure 6, 38 is employed to verify the performance and usefulness of the proposed approach.…”
Section: Data and Case Studymentioning
confidence: 99%
“…Let the starting time be t s = 540 th minute then its ending time will be the 570 th minute. To get information about each and every appliance of all consumers, e.g., input parameter, upper and lower bound, budget, etc, an aggregator should be installed at consumer's premises shown in Figure . The aggregator collects all the information about appliances operation, their operating time interval, HIF, type of appliance, consumer's availability, appliances priority, and preferences.…”
Section: Rem Problem Statementmentioning
confidence: 99%